Online Course Satisfaction and Continuance Among Materials Science and Engineering Students - Zou, Ying (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study examines the key factors influencing online course satisfaction and continuance intention among undergraduate students majoring in Materials Science and Engineering at three public universities in Chengdu, China. Research design, data and methodology: A quantitative survey was conducted among 481 undergraduate Materials Science and Engineering students from three public universities in Chengdu, China. A validated questionnaire using a five-point Likert scale was developed, with reliability confirmed via pilot testing. Data were analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) to examine relationships among key variables. Results: The findings indicate that all hypotheses were supported, with satisfaction having the most significant impact on continuance intention. This highlights that online education has become an essential aspect of university competitiveness. Investigating online course satisfaction and continuance intention can help universities develop more attractive online course systems, thereby enhancing their brand influence. Conclusions: The study’s findings provide data-driven support for educational policymakers, helping local education authorities formulate more practical policies related to online education and promote educational reform. This research can assist educational institutions in improving online course design, enhancing the learning experience, and advancing educational modernization. Additionally, it offers insights into market trends and the future development of the education sector.